Drastic method to map groundwater vulnerability to pollution using nitrate measurements in agricultural areas - Samara, T.; Yoxas, G. (Bulletin of the Geological Society of Greece, 2013)
DRASTIC model has been used to map groundwater vulnerability to pollution in many areas. Since this method is used in different places without any changes, it cannot consider the effects of pollution type and characteristics. Therefore, the method needs to be calibrated and corrected for that aquifer and specific land use. In this research, by correcting the rates of DRASTIC parameters, one can assess the vulnerability potential to pollution more accurately. The new rates were computed using the relationships between DRASTIC INDEX (DI) corresponding to land use and to nitrate concentration in groundwater. The proposed methodology was applied in deltaic region of alluvial aquifer of Volinaios catchment located in the northwestern part of Peloponnesus. In order to determine the quality of the ground waters, either for watering or irrigating purposes, in the study area, a sampling was made. Correlation was used to find the relationship between the index and measured pollution in each point and therefore, to modify the rates. The results showed that the modified DRASTIC is better than the original method for nonpoint source pollution in agricultural areas.